Pengembangan Desain Pelatihan Penggunaan Digital Learning Platform Bagi Mahasiswa Bidang Pendidikan - Nadya Fadillah F; Aditya Pratama; Susan Febriantina (Peneliti.net, 2021)
The study aim of this reasearch was to developed a training design for the application of the Digital Learning Platform in learning for students in the field of education at the Faculty of Economics, Jakarta State University. The data were collected through participant observation using questionnaire. The participants are students of the Faculty of Economics, Jakarta State University who will take part in the student skills program (PKM) at school. The design develompment use ADDIE model with modified and integrated with research method R&D of level 1 which has validation by internal validaty. In order to be validated in the academic and scientific, the resulting model have tested by internal validation through three experts, named experts judgment, by expert of training design, expert of material, and expert of media. The result showed that the model design get average score 92,37% from experts, which is valid and ready to implement to the next step.